ИСЛАМ СУФИЗМ (ТАСАВВУФ) ФИЛОСОФИЯНЫН КЭЭ БИР МАСЕЛЕЛЕРИ - Масиралиев, Ш. П. (Scientific Journal of Faculty of Theology, 2015)
Sufism, the presence of God's unity and the unity of the universe formed (Unity), describing the religious and philosophical understanding. Sufism as a system thinking, after Islam was founded by the Arabs (Tekkeler, Zavieler,) the name of the school, as well as a number of Iranian and Turkish thinkers have developed the use of ancient Greek thought took the form of the theory. Sufism, as well as God, the universe and human vision, and people with God in general, people with other people, their relationships with people in the search for and description of the whole path is defined as Sufism.